1998
DOI: 10.1046/j.1365-2478.1998.750311.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting non‐orthogonal split shear waves for seismic anisotropy in multicomponent VSPS

Abstract: There are two main sources of non‐orthogonality in multicomponent shear‐wave seismics: inherent non‐orthogonal split shear waves arising from substantial ray deviation in off‐symmetry planes due to strong anisotropy or complex overburden, and apparent non‐orthogonal split shear waves in the horizontal plane due to variation of the angle of incidence even if the two shear waves along the raypath are orthogonal. Many techniques for processing shear‐wave splitting in VSP data ignore these kinds of non‐orthogonali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This is due to the significant scatter in ϕ measurements (Figure S16), while a secondary ϕ maximum at a SW-NE direction, that would be in agreement with previous studies, is also observed. The existence of two groups of ϕ measurements at stations PYRG and HELI indicates either a strong spatial dependence or that shear-waves propagate through two distinct media with different anisotropic properties [21,77,78].…”
Section: Seismic Anisotropy In the Wgocmentioning
confidence: 99%
“…This is due to the significant scatter in ϕ measurements (Figure S16), while a secondary ϕ maximum at a SW-NE direction, that would be in agreement with previous studies, is also observed. The existence of two groups of ϕ measurements at stations PYRG and HELI indicates either a strong spatial dependence or that shear-waves propagate through two distinct media with different anisotropic properties [21,77,78].…”
Section: Seismic Anisotropy In the Wgocmentioning
confidence: 99%
“…The abovementioned vector wavefield separation methods all imply that the P-waves and S-waves are orthogonally polarized, and this assumption is generally not valid for an anisotropic medium [82]. For the wavefield separation problem of non-orthogonal P-waves and S-waves in an anisotropic medium, Lei [33] and Lu et al [34] discussed this problem from the perspective of natural earthquakes and exploration seismology and provided a solution.…”
Section: The Vector Separating Methods Of the P-wave And S-wavementioning
confidence: 99%
“…is general in that it can represent cases with fewer than three non‐orthogonal vectors, reducing to of Li et al (1998) in the case of two vectors in horizontal plane.…”
Section: Separation Of Polarization‐vectors Of Body Waves On Three‐mentioning
confidence: 99%
“…Seismic anisotropy exists almost everywhere in the earth medium (Crampin & Booth 1985; Crampin 1987, 1989; Yao et al 1992; Bouin et al 1996; Song & Richards 1996; Lei et al 1997; Wolfe & Silver 1998; Fouch et al 2000; Christensen et al 2001). While polarizations in homogeneous isotropic medium are mutually orthogonal, polarizations of body waves in anisotropic medium are usually not (Crampin & Booth 1985; Crampin 1991; Li et al 1998). Progress in dealing with non‐orthogonal shear‐waves on horizontal components under some special conditions in anisotropic medium has been made (Li & Crampin 1993; Li et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation